Terrorism And Counter-Terrorism In India: A Critical Evaluation Of The Legal And Policy Framework (Journal of Namibian Studies : History Politics Culture, 2023)
This research article critically evaluates the legal and policy framework surrounding terrorism and counter-terrorism in India. It examines the effectiveness of current laws and policies in addressing the challenges posed by terrorism, with a focus on human rights implications and the balance between security measures and civil liberties. The article also analyzes the role of international cooperation in combating terrorism and proposes recommendations for enhancing the legal and policy framework to better respond to evolving threats.